1995
DOI: 10.3186/jjphytopath.61.513
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Relationships between Rice Black-streaked Dwarf and Maize Rough Dwarf Fijiviruses Detected by Nucleic Acid Hybridization.

Abstract: By polyacrylamide gel electrophoresis (PAGE) and nucleic acid hybridization, the extent of genomic relatedness between rice black-streaked dwarf Fijivirus (RBSDV) and maize rough dwarf Fijivirus (MRDV) was investigated. It was previously reported that RBSDV S7 and S8 correspond to MRDV S6 and S7, respectively, based on nucleotide sequences (Marzachi et al., Virology, 1991). However, present comparison of the genomic segments of the two viruses in polyacrylamide gel electrophoresis together with the hybridizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Prehybridization and hybridization were performed using the method described by Isogai et al (1995).…”
Section: Methodsmentioning
confidence: 99%
“…Prehybridization and hybridization were performed using the method described by Isogai et al (1995).…”
Section: Methodsmentioning
confidence: 99%
“…During the preparation of this manuscript, the partial S1-S10 genomic sequences of a Spanish isolate of MRDV were also made public (accession numbers LK392325-LK392343; Achon et al, 2015). Th e Italian and Spanish isolates share more than 95% identities with each other at both the nucleotide and amino acid levels and S7-S10 of both isolates share 95.6-99.7% nucleotide and amino acid identities with the partial sequences of the isolates previously described by Marzachi et al (1991Marzachi et al ( , 1995, although those earlier sequences appear to be wrongly labelled: those labelled S6 and S7 should be reassigned as S7 and S8, respectively, as fi rst proposed by Isogai et al (1995) on the basis of hybridization experiments.…”
Section: Discussionmentioning
confidence: 73%
“…All known fi jiviruses contain ten linear genomic segments of double-stranded RNA (dsRNA), ranging in size from approximately 1.4 to 4.5 kb and named S1-10 according to their migration in PAGE, and most of them replicate in their plant hosts, where they induce growth abnormalities. Previous extensive studies have shown that the four viral pathogens of MRDD are closely related to each other and similar in particle morphology, genomic profi le, and serological relationships (Luisoni et al, 1973;Milne et al, 1973Milne et al, , 1977aReddy et al, 1975Reddy et al, , 1983Isogai et al, 1995;Zhang et al, 2001a,b;Distéfano et al, 2002Distéfano et al, , 2003Distéfano et al, , 2005Distéfano et al, , 2009Guzmán et al, 2007, Wang et al, 2010. All these viruses naturally infect maize and cause similar symptoms on maize or other host plants (Milne et al, 1977a;Attoui et al, 2012).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…S1 contained the major motifs characteristic of an RNA-dependent RNA polymerase (RdRp) (10), which can be aligned with those from the RdRp proteins of other reoviruses and which is thought to be a minor component of the core particle. RBSDV, MRDV, RBSDV-2, and MRCV were always closely clustered together in phylogenetic analyses of their segments, and the new sequences of MRDV will be important for determining the appropriate taxonomic positions of these viruses, which sometimes have been considered isolates of a single species (11). …”
Section: Genome Announcementmentioning
confidence: 99%